Antibacterial activity of chitosan nanofiber meshes with liposomes immobilized releasing gentamicin. (May 2015) - Monteiro, Nelson; Martins, Margarida; Martins, Albino; Fonseca, Nuno A.; Moreira, João N.; Reis, Rui L.; Neves, Nuno M.
Graphical abstract: Abstract: Chitsan (Ch) nanofiber mesh (NFM) is a material with natural characteristics favoring its use in human wound dressing. The present work proposes a gentamicin-loaded liposome immobilized at the surface of Ch NFMs to promote its antibacterial activity. To achieve this purpose, Ch NFMs were functionalized with thiol groups, and gentamicin-loaded liposomes were covalently immobilized by the reaction of the SH groups with maleimide. The maximum concentration of SH groups (55.52 ± 11.19 nmol cm −2 ) was obtained at pH 7. A fluorescent dye was covalently bound to the SH groups present at the surface of electrospun Ch NFMs. Their spatial distribution was uniform throughout the NFMs when analyzed by fluorescence microscopy. Gentamicin was successfully encapsulated into the liposomes with an efficiency of 17%. Gentamicin-loaded liposomes were uniformly distributed at the surface of the Ch NFMs and the drug release kinetic showed a sustained release of gentamicin during 16 h, achieving a steady state at 24 h. The in vitro susceptibility tests confirmed that the gentamicin released from the liposomes immobilized at the surface of electrospun Ch NFM has bactericidal activity against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus . The results show that the developed system has promising performance for wound dressing applications, avoiding infections caused by these common pathogens.